2010
DOI: 10.18777/ieashc-task42-2010-0001
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art of Digital Tools Used by Architects for Solar Design

Abstract: This report presents a review of existing digital tools widely used today, as part of the Subtask B: Methods and Tools for Solar Design of the IEA SHC Task 41 "Solar Energy and Architecture". The review covers a total of 56 computer programs, classified according to three categories: 1) CAAD (computer-aided architectural design), 2) visualization, 3) simulation tools. The aim of this review is to analyse the current software landscape for building projects with a focus on early design phase (EDP). CAAD tools U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…However, with the enormous increase in the available computational power since then and further improvements and optimisation of the original method [101] [102], the additional computational expense of a full spectral simulation in comparison with an RGB model is almost negligible. As also noted in [17] spectral rendering is a promising development for future study of special coating and/or glazing materials widely used in solar architecture. Therefore, it can be concluded that the spectral rendering has become a reasonable and necessary step forward in visualisation, daylighting and BIPV simulation.…”
Section: Spectral Renderingmentioning
confidence: 90%
See 2 more Smart Citations
“…However, with the enormous increase in the available computational power since then and further improvements and optimisation of the original method [101] [102], the additional computational expense of a full spectral simulation in comparison with an RGB model is almost negligible. As also noted in [17] spectral rendering is a promising development for future study of special coating and/or glazing materials widely used in solar architecture. Therefore, it can be concluded that the spectral rendering has become a reasonable and necessary step forward in visualisation, daylighting and BIPV simulation.…”
Section: Spectral Renderingmentioning
confidence: 90%
“…On the other hand, the majority of the visualization tools almost completely abandoned quantitative aspects of the simulations including daylighting and put a focus only on a visualisation part. Yet, according to trends, majority of tools that aim for physically based approach would sooner or later strive to unite artistic and scientific needs into versatile crossindustry packages, as it has already happened in automotive and aerospace industries and their cutting edge software like SPEOS, VRED etc.. Dubois and Horvat [17] also recognized that this is certainly an area which needs much development in the future. It is just a question of time before this approach becomes common in architecture/building industry.…”
Section: Types Of Simulations/analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The target audience is architects. The tool's major strengths are its visual appearance and suitability for early design stages (refer Fig.6) [9].…”
Section: Ecotectmentioning
confidence: 99%
“…The program therefore only requires a minimum of input data in order to perform initial sun shading studies and preliminary assessments as shown in Fig.7. As the design process continues, the amount of data input into the model can be increased, allowing acoustic and thermal simulations and resource modeling [9].…”
Section: Import/export [9]mentioning
confidence: 99%